ANALISIS MANAJEMEN HUTAN ADAT DI DESA TORO KECAMATAN KULAWI KABUPATEN DONGGALA - Hamzari Hamzari (Universitas Tadulako, 2008)
The research aimed to formulate a custom forest management compliance with forest land functions in the Toro custom forest area according to forest land functions. The analysis method implemented for formulating the custom forest management is a comparative analysis, with which the land categorization concept according to Toro custom norms was compared with the forest management concept according to the Government Regulation Number 6, 2007. The research results showed that the Toro custom community has already got hold of the knowledge system about land use management based on land biophysical characteristics. In terms of area management aspect, there was indistinct forest management yet in the field among various kinds of custom land categorization implemented. Meanwhile in forest management aspect, particularly in custom forest area utilization, there was a difference in term of the interests between the custom land categorization and the government regulation number 6, 2007.